Diretrizes para a conservação da estância do Batovi/São Gabriel – RS - Fert, Fernando Buzati (2011)
“Estâncias” are the establishments dedicated to livestock found in the Região Platina of South America. These establishments have an important role in the shaping of rio-grandense society, were also considered the ancestral home of the typical element of the region: the “gaúcho”. This establishments preservation and recognition as cultural heritage are of great importance to the knowledge and reflection about the history of the southernmost brazilian state. The aim of this work is to define guidelines for the conservation of Estância do Batovi, located in the municipality of São Gabriel, Rio Grande do Sul State, Brazil, and to contribute to the conservation not only the object of study, but also assist the appreciation of similar historical sites, emphasizing the knowledge of the past to understand the present and project the future. The methodology used was suggested by the Burra Charter and the cultural value of the subject was identified and evaluated as of great importance to the community in which it is inserted. Through the preparation of a Statement of Cultural Significance to the site were defined actions for its conservation for future generations, resulting in a Statement of Conservation Policy for the Estância do Batovi. Due to the good shape in which the site lies, were primarily intended actions of maintenance for it is preserved as a landmark of local history.